Annphenone from Artemisia vestita Inhibits HepG2 Cell Proliferation - Long, Anhua; Fu, Jie; Hu, Yang; Luo, Yin (Asian Journal of Chemistry, 2013)
Artemisia vestita is a common traditional Tibetan medicinal plant which has been widely studied for its antiinflammatory activity. However, little is known about its antitumor activity. The present study performed a bioassay-guided isolation to isolated annphenone from A. vestita, which showed potent and specific antiproliferative activity against HepG2 cells with the half maximal inhibitory concentration (IC50) value of 2.0 ± 0.4 μg/mL. Cell cycle analysis showed that annphenone arrested HepG2 cells in G0/G1 phase. Immunocytochemistry dectection suggested that annphenone could inhibit the expression of b-catenin and induce its localization transfer, thereby reducing the expression of cyclin D1 protein. Molecular docking study indicated annphenone was a possible ligand of asialoglycoprotein receptor (ASGP-R), which was related with its selectivity for HepG2 cells. Therefore, annphenone was a potential specific antiproliferative agent against hepatocellular carcinoma cells.